Strategi Humas Universitas Dalam Meningkatkan Minat Calon Mahasiswa Baru Di Universitas Sari Mutiara Indonesia - Exmin Man Jaya Laia; Sozanolo Hulu; Open Berkat (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
The aim of this research is to examine the public relations strategies of the university in increasing the interest of prospective new students at Sari Mutiara Indonesia University and to identify the supporting and inhibiting factors for public relations in enhancing the interest of prospective new students. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that public relations strategies are implemented by: publishing campus achievements, such as accreditation, teaching staff, and academic achievements at various levels; establishing cooperation with the media. Supporting factors include internal and external elements, while inhibiting factors arise from internal communication challenges.